Leveling the Field: Gender Inequity in Academia During COVID-19 - Shalaby, Marwa; Allam, Nermin; Buttorff, Gail J. (PS, political science & politics, 2021)
This article explores the differential impact of the COVID-19 pandemic on the productivity of male and female academics and whether the ongoing health crisis will exacerbate further the existing gender gap in academia in both the short and long terms. We present early evidence of the pandemic’s disproportionate effect on women’s research productivity using online survey data supplemented by interview data with regional and international female political scientists. The interviews and survey findings reveal gender disparities in perceived research productivity and service workloads during the pandemic. The results also shed initial light on the pandemic’s impact on the research productivity of academics who are parents, especially among women.